2019
DOI: 10.1108/jm2-05-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

The relational model of entrepreneurship and knowledge management toward innovation, strategy implementation and improving Islamic boarding school performance

Abstract: Purpose The influence of entrepreneurial orientation and knowledge management on innovation, the influence of knowledge management on the implementation of strategies and the influence of entrepreneurial orientation, knowledge management, innovation, implementation of strategies to organizational performance, where the organization referred to is an Islamic boarding school. Design/methodology/approach This research applied quantitative causal design and was an explanatory research. It was conducted at an Isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 43 publications
8
57
1
5
Order By: Relevance
“…This result aligns with other previous studies that confirmed the positive and significant impact of strategic planning on OP (Al-Dhaafri and Al-Swidi, 2016;Donkor et al, 2018;Fadol et al, 2013;Glaister et al, 2008;Hill et al, 2014). The result of the second hypothesis about the relationship between strategy implementation and OP also was supported (b = 0.182, t = 3.127, p < 0.01) and align with other previous results (Joanna et al, 2014;Rapert et al, 2002;Rofiaty, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…This result aligns with other previous studies that confirmed the positive and significant impact of strategic planning on OP (Al-Dhaafri and Al-Swidi, 2016;Donkor et al, 2018;Fadol et al, 2013;Glaister et al, 2008;Hill et al, 2014). The result of the second hypothesis about the relationship between strategy implementation and OP also was supported (b = 0.182, t = 3.127, p < 0.01) and align with other previous results (Joanna et al, 2014;Rapert et al, 2002;Rofiaty, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Geertz describes pesantren as the pinnacle of old-fashioned culture, which is more focused on morality or behavior that is in accordance with religious teachings and being obedient to the teacher, such as accepting everything that happens to him and life where everything has been arranged by Allah, this is what is assumed Gerrtz about pesantren (Rofiaty, 2019). In contrast to the researchers who came after him, Dawan Raharjo, Manifred Ziemek, and Horikoshi, they describe it as a dynamic institution that encourage modern social change (Amri, Tahir, & Ahmad, 2017).…”
Section: Pesantren As a Place Of Islamic Cultural Heritagementioning
confidence: 99%
“…Santri now only have to enjoy all the facilities and services of the pesantren and just study. Meanwhile, the facilities and services provided by the students or those provided by the pesantren (Rofiaty, 2019).…”
Section: Madurese Pesantren As Halal Tourist Sitementioning
confidence: 99%
“…Three, private Diniyah Schools as part of the education system in Indonesia are known for their presence in providing services to middle and rural communities, which emphasize Islamic learning and ethics [35]. The importance of Diniah's school made the Sumenep Government issue Perbup No.…”
Section: Education Policy and Implementationmentioning
confidence: 99%